INACTION OF THE ARBITRATION MANAGER TO REPLENISH THE BANKRUPTCY ESTATE AND THE RESULTING CONSEQUENCES - DAVAEVA G.S. (Legal Bulletin)
Based on the analysis of judicial practice in bankruptcy cases, the article examines one of the most common grounds for bringing an arbitration manager to civil liability - causing losses to creditors due to the inaction of the bankruptcy trustee to fill the bankruptcy estate. The statistics of recent years on the number of cases of recovery and amounts recovered from managers for various reasons are given. The purpose of the scientific work is to analyze the norms of the current legislation related to the status of the arbitration manager, his duties to take the necessary measures that will contribute to the maximum filling of the bankruptcy estate and liability arising in case of violation of established legal requirements, as well as established legal opinions used in the practice of arbitration courts. The problems related to the failure of the arbitration manager to take measures to challenge transactions, as well as to recover receivables, are considered. The issue of possible development of the institution of bringing the arbitration manager to responsibility in the form of recovery of losses in case of adoption of new amendments to the Bankruptcy Law is analyzed. The methods used. In the course of writing the scientific work, both general scientific and various special legal methods (statistical method, comparative legal, structural analysis) were used.